First Do No Harm: Moving Beyond Universal Preprocedural Testing for COVID-19. (24th June 2021) - Penney, Jessica; Shah, Sajani; Doron, Shira
Abstract: Preprocedural testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was introduced early in the pandemic in an effort to protect health care workers, direct appropriate use of personal protective equipment (PPE), and improve patient outcomes. In light of our appreciation for the efficacy of PPE and the nuances associated with interpretation of polymerase chain reaction testing for SARS-CoV-2, particularly as community transmission decreases, we call for a re-evaluation of universal preprocedural testing. We propose a transition to a patient-centered approach, focusing on testing patients whose outcomes would be improved by a delayed procedure in the event of a positive test and a greater reliance on appropriate PPE rather than preprocedural test results. We recommend that a community infection rate threshold be set at which point preprocedural testing is discontinued, understanding that there is an inflection point at which testing downsides outweigh the benefits.